Aspectos processuais e penais dos crimes de computador - Torre, Marina Giantomassi Della (2009)
We live in the midst of a technological revolution. In the wake of innovation, a traditional and conservative judicial order faces, simultaneously, an old and new reality. While the old reality is based on concepts and habits either built or resulting from facts and activities that can be perceived and identified; the new reality is based on a virtual mean, where new relationships arise (not necessarily connected to the real world), requiring new concepts and interpretations. The use of telematics leads to a considerable change in the habits of those who make use of it, enabling their definitive inclusion in an increasingly dynamic world. The emergence of telematics poses many challenges in the Law field. Among the main ones, we highlight the need to establish regulation for criminal conducts carried out in this mean. Given its characteristics, it requires the establishment of a paradigm for preventive control, in addition to severe repressive means. Using the relationships between Brazilian law, comparative law, discussions of doctrine and jurisprudence and proposals of this new scenario, we seek to analyze a set of questions, including juridical goods affected by telematics crimes; supposed criminals and their victims; and problems related to their types and competencies. The identification of authors and relative relevancies are also needed for this new and complex fashion of crimes: technology crimes resulting from a new global and risky information society. Lastly, seeking to protect the principles of the Federal Constitution, both the citizen and State s fundamental rights and guarantees must be secured, reinforcing the base of the Democratic State of law. This must be done through a judgment consideration that observes the proportionality principle, in every single situation that requires investigation and punishment of crimes of this nature